RADIATION DETECTOR FOR THE ISRAELI FIRST RESPONDERS—METHODOLOGY OF SELECTION. Issue 1 (4th November 2022) - Brandis, Michal; Rabby, Yossi; Epstein, Lior; Datz, Hanan; Tsvitman, Eyal; Amit, Gal; Hershkovich, David; Krasner, Esther
Abstract: This paper presents the rationale and development of a methodology of selection of a radiation detector that can be used by first responders arriving to a terror event scene, not knowing if the event involves any radioactive materials. This detector can be used to detect and quantify the presence of gamma radiation. The role of this detector in a radiological terror event is reviewed via the operational concept for handling radiological terror in Israel. The development of the methodology of selection included a literature survey of relevant radiation detector categories, followed by a user-side survey of requirements based on the first responders' experience along with the Israeli Ministry of Defense perspective on the management of radiological events, supplemented by the input from experts in aspects of radiation detection, radiation protection and dosimetry from the Israel Atomic Energy Commission's Soreq Nuclear Research Center. The general qualitative characterisation of requirements was then quantified using a scoring method, enabling the methodological evaluation and numerical ranking of available detectors. Plans to evaluate candidate detector models according to the developed methodology are outlined. The detectors evaluation will be conducted as part of the procurement procedure of future detectors for first responders.